Pemanfaatan Peninggalan Sejarah Kota Medan dalam Pembelajaran Sejarah di Sekolah Menengah Atas Negeri (SMAN) 11 Kota Medan - Humairah, Siti; Nababan, Surya Aymanda; Muhammad Adika Nugraha; Saragih, Ridho Gilang Amalsyah (Medan Resource Center, 2023)
An introduction to history in Indonesia may be familiar. Historical relics and other phenomenal stories can provide important lessons in history. Researchers conducted research at State High School (SMAN 1) 11 Medan. This research explores the use of the historical heritage of the city of Medan in history learning at SMA Negeri 11 Medan. The city of Medan, as a rich historical and cultural center, has a historical heritage that can enrich students' learning experiences. This research aims to identify the potential for using these historical relics in the school history curriculum, as well as analyzing their impact on students' historical understanding and interests. Through this approach, it is hoped that history learning at SMA Negeri 11 Medan can become more interesting and relevant, as well as provide a deeper understanding of local history. The results of this research can provide insight and guidance for educators to improve history teaching in the school environment. Researchers also see that there is an important role in knowing integrity and success through learning history so that students will feel more capable of understanding the genealogy of a region based on its historical sequence. It is hoped that through this research, both researchers and readers will love and appreciate the history of Medan City more through learning history at SMAN 11 Medan.